2022
DOI: 10.3389/fneur.2022.782286
|View full text |Cite
|
Sign up to set email alerts
|

The Triglyceride Glucose Index Is a Risk Factor for Enlarged Perivascular Space

Abstract: The triglyceride glucose (TyG) index is considered a simple surrogate marker for insulin resistance and has been associated with cerebrovascular diseases. However, limited information is available regarding its association with the subclinical cerebral small vessel disease (CSVD). Here, we investigated the association of TyG index with the burden and distribution of enlarged perivascular space (EPVS) in the non-diabetic population. The data of 531 non-diabetic patients from 2017 to 2020 were assessed. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…In another study, hypertriglyceridemia was found to be associated with reduced leukoaraiosis in patients with a small vessel stroke [3] but not other lipid fractions. A recent study among nondiabetic adults investigated the relationship between total cholesterol, LDL, HDL, and moderate to severe dPVS and, like our study, showed nonsignificant after multivariate comparison [26].…”
Section: Discussionsupporting
confidence: 49%
“…In another study, hypertriglyceridemia was found to be associated with reduced leukoaraiosis in patients with a small vessel stroke [3] but not other lipid fractions. A recent study among nondiabetic adults investigated the relationship between total cholesterol, LDL, HDL, and moderate to severe dPVS and, like our study, showed nonsignificant after multivariate comparison [26].…”
Section: Discussionsupporting
confidence: 49%
“…Second, insulin resistance is a key pathological process during the development of CSVD [24,32]. Predictably, TyG index has been proved to be positively associated with a higher prevalence and burden of CSVD [9,[33][34][35][36], which was reported to predict a recurrent ischemic stroke or intracerebral hemorrhage in numerous studies [1,[37][38][39][40][41]. CSVD could make a contribution to the mechanism of increasing ischemic stroke recurrence by a higher TyG index.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies [ 15 17 ] only discussed LCI-related risk factors such as renal function. However, these studies only identified risk factors closely associated with LCI and did not integrate these risk factors into a model to predict LCI.…”
Section: Discussionmentioning
confidence: 99%